Estimation of erosion phenomena within helicon plasma sources through a steady-state explicit analytical model - Del Valle , Juan I.; Granados , Víctor H.; Chang Díaz, Franklin R. (Frontiers in Physics, 2022)
Helicon plasma sources produce high-density discharges without the need of electrodes in direct contact with the plasma, which is thought to provide them with long operational lifetimes. An explicit steady-state analytical model is described with the capability of depicting the 2D plasma density distribution, the sheath potentials and the estimated sputtering and etch rates along the plasma-facing components of the source. The individual constituting submodels are fitted against available experimental data, and the model is used to predict erosion rates within the VX-CR research helicon plasma source. Erosion within these components is dependent on the value of plasma density along the boundaries, the electron temperature and the particular ion-target material combination. The highest erosion rates are found along the upstream system boundary, followed by the regions near the helicon antenna straps where a capacitive RF sheath is formed. The assumptions and limitations of the model are discussed, and future improvements are proposed.